On The Distribution Of Perfect Numbers And Related Sequences Via The Notion Of The Disc - Agama, Theophilus (My University, 2022)
In this paper we investigate some properties of perfect numbers and associated sequences using the notion of the disc induced by the sum-of-the-divisor function $\sigma$. We reveal an important relationship between perfect numbers and abundant numbers.
Keywords: perfect numbers; disc; divisor